Professional Fees and Other Direct Costs in Chapter 7 Business Liquidations - Robert M. Lawless; Stephen P. Ferris (Washington University Law Quarterly, 1997)
Here we provide a comprehensive look at direct costs associated with chapter 7 business bankruptcy liquidations by examining cases from five geographically dispersed judicial districts. This Article measures chapter 7 direct costs, which are essentially out-of-pocket administrative costs associated with chapter 7 proceedings. Examples of direct costs include attorneys' fees, filing fees, and other professional fees. Part II describes the procedures we followed in gathering data. Part II also sets forth several assumptions we made when describing direct costs. Each time an assumption needed to be made, we took the assumption that produced the lowest bankruptcy costs. Accordingly, the data in this Article is a conservative estimate of chapter 7 costs. Part III describes the characteristics of the debtors and cases in our sample. Part IV discusses the actual cost measurements and quantifies the costs of chapter 7 business bankruptcy. Part V uses statistical analysis to identify determinants of chapter 7 costs. Part VI summarizes our major conclusions.
Keywords: Small business; Liquidation; Administrative fees